Death Associated to Methicillin Resistant Staphylococcus aureus ST8 Infection in Two Dolphins Maintained Under Human Care, Italy - Mazzariol, Sandro; Corrò, Michela; Tonon, Elena; Biancani, Barbara; Centelleghe, Cinzia; Gili, Claudia (Frontiers in Immunology, 2018)
The present study describes the isolation of Methicillin-resistant Staphylococcus aureus (MRSA) from respiratory tract of 2 dolphins of different origin, a stranded juvenile Risso’s dolphin (Grampus griseus) and a captive born common bottlenose dolphin (Tursiops truncatus) calf, which died in the same institution at one-month distance from the other. A complete microbiological and genetic investigation confirmed the presence of MRSA clone-complex 8, sequence type (ST) 8, spa-type t008 in both individuals. This strain differs from the one previously reported in walruses and dolphins and has never been described in dolphins before, but it is randomly isolated from Italian human patients. Vertical transmission of the infection may also occurs in other species and considering the description and location of the pathological lesions, this seems to be the most likely route of transmission implied in the young bottlenose dolphin. Staphylococcus aureus is known as an opportunistic agent, usually secondary to other pathogens, but its multiple antibiotic resistance and its zoonotic implications suggest a thorough and strict application of animal management hygiene protocols.